The Effect of Indirect Method on the Tenth Grade Students' Grammar Achievement at SMAN Ambulu - Crismonita, Wika Fujianti; Tasnim, Zakiyah; Fitriyah, Siti Masrifatul (EFL Education Journal, 2022)
This research was an experimental research. The purpose of this study was to know whether or not there was a significant effect of the use of Indiret Method on the grammar achievement of the tenth grade students of SMAN Ambulu. The design of this study was quasi experimental with Post-test only design. The treatment was given to the Experimental group that was taught grammar by using Indirect Method while the Control group was taught grammar by using Direct Method, the method used by the teacher in the actual classes. The primary data of this research were obtained from the students’ score of grammar test. The data were analyzed by using t-test formula. The calculation result with significant level of 5% showed 0.03 value, which was lower than 0.05. It means that the null hypothesis (HO) was rejected while the alternative hypothesis (Ha) was accepted. It can be concluded that there was a significant effect of using Indirect Method on the Grammar Achievement of the Tenth Grade Students at SMAN Ambulu. Therefore, the English teachers are recommended to apply Indirect Method when teaching grammar.